Analis Perlindungan Hukum Bagi Kreditur Terhadap Kepailitan Debitur: Studi Putusan Pengadilan Niaga Surabaya - Purba, Riski Jaya; Budiman, ⁠Anwar; Wiryadi, Uyan (VISA: Journal of Vision and Ideas, 2025)
Bankruptcy is a solution that can be used to resolve debt and receivable problems that are pressing on a debtor. This situation occurs when the debtor no longer has the ability or goodwill to pay his debts to his creditors. The problems discussed in this research What is the legal protection for creditors if the debtor experiences bankruptcy? What is the mechanism for the process of resolving bankruptcy cases until creditors obtain their rights? Normative juridical research methods. In conclusion, the declaration of bankruptcy of PT Corpus Asa Mandiri as debtor, and the rejection of the cassation application against the bankruptcy decision is a form of legal protection of the interests of creditors' rights. The mechanism for resolving the management and settlement of the bankrupt debtor's assets (bankruptcy boedel) is basically the treatment of all the bankrupt debtor's assets, both real and potential, in order to restore the rights of creditors. Completion of the management and settlement of a bankruptcy debtor is nothing more than an activity or action relating to the continuation of the distribution of assets which are declared legally valid as a bankrupt debtor's property.